Improving Student Learning Achievement in Aqidah Akhlak Learning with The Card Sort Method at MTs Muhammadiyah Panyakalan - Mawati, Yelmi; Faqori, Yudha Bima; Sulaeman, Wono; Suryani, Yani; Risman, Mulia (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to improve the learning achievement of Aqidah Akhlak of class VII students of MTsM Panyalan on the material "Avoiding Reprehensible Morals" by using the Card Sort method. This study is a classroom action research conducted in two cycles. Each cycle in this study consists of four steps, namely planning, implementation, observation, and reflection. The subjects of the study were 12 class VII students consisting of 5 male students and 7 female students. The results of the study showed a significant increase in student learning achievement after the implementation of the Card Sort method. In cycle I, the percentage of student learning completion reached 50%, while in cycle II it increased to 83.33%. This method succeeded in increasing student activity and involvement in learning, as well as making it easier for students to understand material related to reprehensible morals through grouping and group discussions. The application of the Card Sort method also showed a positive response from students, who felt more interested and motivated in participating in learning. Therefore, this method can be used as an effective alternative to improve student learning achievement and involvement in learning Reprehensible Morals.